MRI white matter lesion central veins in multiple sclerosis - Samaraweera, Amal Prasanna Rohan (2017)
This thesis focuses on the use of the Magnetic Resonance Imaging (MRI) white matter lesion (WML) central vein as a biomarker for multiple sclerosis (MS). MS remains a clinical diagnosis, with reliance on MRI to support the diagnosis. Misinterpretation of the MRI can lead to misdiagnoses of diseases that mimic MS. With the increase in disease modifying treatments, accurate and timely diagnosis is needed now more than ever.